Romania : Financial Sector Assessment Program-Technical Note-Balance Sheet Analysis. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Note analyzes the macro-financial interlinkages, sectoral dependencies, and potential balance sheet vulnerabilities for all resident sectors in Romania. The financial sector size and interconnectedness have been increasing significantly. The overall amount of intra-financial sector exposures grew from five percent of GDP in 2008 to approximately seven percent of GDP in 2016. The banking system is at the center of intra-financial sector balance sheet connections, as an overall net borrower that channels funds to other domestic sectors. The funding of bank liabilities by domestic financial institutions has been rising and stood at close to 10 percent of banks' nonequity liabilities in 2016. Moreover, banks are also exposed on the credit side to nonbank financial institutions, in particular to other financial institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet